Head teachers' attitudes towards religious diversity and interreligious dialogue and their implications for secondary schools in Catalonia - Baños, Ruth Vilà (British Journal of religious education, 2020)
This paper explores the attitudes of secondary-school head teachers towards religious diversity, intercultural and interreligious dialogue and the role of education in fostering intercultural and interreligious dialogue. A sample comprising 275 head teachers in Catalan secondary schools answered an online questionnaire. The results revealed attitudes which were moderately favourable towards cultural and religious diversity, more strongly favourable towards interreligious dialogue, and less favourable towards education playing a major role in managing religious and cultural diversity and in fostering interreligious dialogue. We found significant differences in head teachers' attitudes in line with the specific features of the schools where they worked. Amongst these differences, it was noticeable that heads of religious and private-public schools had more positive attitudes towards managing religious and cultural diversity and towards education playing a leading role in promoting dialogue. Also, we identified three groups of head teachers who showed differing degrees of positivity according to the perceived religious diversity of their schools. The more diverse the school, the less favourable the attitude, and vice-versa; the most moderate favourability was also associated with the most moderate diversity.